Emerging roles of interferon-stimulated gene-15 in age-related telomere attrition, the DNA damage response, and cardiovascular disease - González-Amor, María; Dorado, Beatriz; Andrés, Vicente (Frontiers in Cell and Developmental Biology, 2023)
Population aging and age-related cardiovascular disease (CVD) are becoming increasingly prevalent worldwide, generating a huge medical and socioeconomic burden. The complex regulation of aging and CVD and the interaction between these processes are crucially dependent on cellular stress responses. Interferon-stimulated gene-15 (ISG15) encodes a ubiquitin-like protein expressed in many vertebrate cell types that can be found both free and conjugated to lysine residues of target proteins via a post-translational process termed ISGylation. Deconjugation of ISG15 (deISGylation) is catalyzed by the ubiquitin-specific peptidase 18 (USP18). The ISG15 pathway has mostly been studied in the context of viral and bacterial infections and in cancer. This minireview summarizes current knowledge on the role of ISG15 in age-related telomere shortening, genomic instability, and DNA damage accumulation, as well as in hypertension, diabetes, and obesity, major CVD risk factors prevalent in the elderly population.